The status and the problem of Western vocal music teaching in Myanmar - MAI NAY CHI HNIN PWINT OO (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: The study’s overarching goal is to improve the teaching and learning of Western classical vocal music by identifying issues and offering recommendations for how to address them. The research will also consider the advantages of finding solutions to these issues. The primary purpose of this research was to infer the current state of Western vocal music education in Myanmar and investigate effective strategies for addressing these issues within the context of the country’s public school system.Method: interviews, both formally conducted and informally conducted, and participant observation were used as qualitative research methods. There are currently seven full-time and part-time teachers in that area, all of whom have at least two years of experience teaching western vocal styles: two from the Music Centers in Yangon, one from the Music Department at the Myanmar Institute of Theology’s Liberal Arts program, and one from an independent unit.Findings: Through interviews, the researcher discovered that few vocal music teachers had formal voice training and had never had the chance to study music themselves as children. Most of them only used what they had learned from other teachers and their own experience to teach voice to students. None of the voice music instructors also had a bachelor’s degree in music.Implications/Novel Contribution: According to the findings, more regular practice is needed in Myanmar. Since students’ backgrounds and skill levels influence lesson and curricular development, teachers should establish ground rules for student practice. Teachers need to get ahead of the game by preparing the literary works and pieces they will use in the next lesson.